Microarray analysis of the global gene expression profile following hypothermia and transient focal cerebral ischemia - Nagel, Simon; Pfleger, Karin; Grond-Ginsbach, Caspar; Wagner, Simone (Neuroscience, 2012)
Background: Hypothermia is one of the most robust experimental neuroprotective interventions against cerebral ischemia. Identification of molecular pathways and gene networks together with single genes or gene families that are significantly associated with neuroprotection might help unravel the mechanisms of therapeutic hypothermia. Material and Methods: We performed a microarray analysis of ischemic rat brains that underwent 90 min of middle cerebral artery occlusion (MCAO) and 48 h of reperfusion. Hypothermia was induced for 4 h, starting 1 h after MCAO in male Wistar rats. At 48 h, magnetic resonance imaging (MRI) was performed for infarct volumetry, and functional outcome was determined by a neuroscore. The brain gene expression profile of sham (S), ischemia (I), and ischemia plus hypothermia (HI) treatment were compared by analyzing changes of individual genes, pathways, and networks. Real-time reverse-transcribed polymerase chain reaction (RT-PCR) was performed on selected genes to validate the data. Results:Rats treated with HI had significantly reduced infarct volumes and improved neuroscores at 48 h compared with I. Of 4067 genes present on the array chip, HI compared with I upregulated 50 (1.23%) genes and downregulated 103 (3.20%) genes equal or greater than twofold. New genes potentially mediating neuroprotection by hypothermia were HNRNPAB, HIG-1, and JAK3. On the pathway level, HI globally suppressed the ischemia-driven gene response. Twelve gene networks were identified to be significantly altered by HI compared with I. The most significantly altered network contained genes participating in apoptosis suppression. Conclusions: Our data suggest that although hypothermia at the pathway level restored gene expression to sham levels, it selectively regulated the expression of several genes implicated in protein synthesis and folding, calcium homeostasis, cellular and synaptic integrity, inflammation, cell death, and apoptosis.